Improving The Methodology of Passing Practical Classes in Math on The Basis of An Active Approach - Yunusova Gulnoza Abduxalikovna (Academia One, 2024)
The article will talk about the methodology for activating the activities of students on the basis of an active approach in practical classes in mathematics
Keywords: based; information; education; mathematical